Control of photovoltaic power integration based on multi‐terminal VSC–HVDC system. Issue 16 (17th December 2018) - Wang, Lei; Wu, Xiaolong; Hou, Junxian; Wang, Tiezhu
Abstract : In order to solve the problem of long‐distance transmission of large‐scale photovoltaic power stations, a multi‐terminal voltage source converter‐based high‐voltage direct current (VSC–HVDC) system based on a DC voltage‐active power‐AC voltage control strategy, which is connected with photovoltaic power stations, is designed in this study. In order to verify the feasibility of the method, a model of a five‐terminal parallel system is established by MATLAB/Simulink, which includes two photovoltaic power stations and a passive network. A series of simulations are carried out based on the model. The results show that the active power of the system can be automatically balanced when the output power of photovoltaic power stations changes. When the three‐phase short‐circuit fault occurs in power grid, the photovoltaic power stations can still run in a stable state and have better fault ride‐through ability.